Analysis of Student Errors in Solving Mathematical Problems in Algebraic Forms Operation Material Based on Newman's Procedure - Lady Fabiola Kaligis; Philoteus E. A. Tuerah; Rosiah J. Pulukadang (Departement of Mathematics Education, 2023)
This study aims to discover the mistakes made by students, especially class VII students at Koka Christian Middle School, when solving math problems on algebraic operations using the Newman procedure. This research is a type of descriptive research with a qualitative approach. The technique for collecting data used a written test by providing description questions that totaled 3 items and was supported by interviews with students and documentation. The subjects in this study were 16 students in class VII of Koka Christian Middle School who took the written test, and 3 of them were selected to be interviewed after a deliberation process. The results of the study showed that students made errors in solving math problems in the material for algebraic operations based on the Newman procedure, namely: 1). error in understanding the problem, where students need to write down what is known and asked by the problem or make examples in the form of variables. 2). problem transformation errors, where students cannot determine the mathematical model of the given problem or cannot determine the correct formula. 3). process skill errors, where students need clarification in the problem-solving steps due to errors in understanding the concept of algebraic operations. 4) final answer errors, where these errors result because students are wrong in the problem-solving process.